Electrical conductivity patterns along transects over the Indian lithospheric domains of differing temporal evolution: a review - Gokarn, S.G. (My University, 2003)
Magnetotelluric studies conducted in different tectonic settings over the Indian lithosphere are discussed here. Studies in the granite-greenstone regions of the Dharwar craton show a high conductivity of about 20 Ω-m beneath the western Dharwar region at depth of about 70 km extending up to depth of more than 160 km. This conductive region shows a predominantly N-S extension with a width of about 100 km along the E-W direction and is interpreted as a possible path of the Reunion Hot Spot. Studies over the Narmada Son lineament and Satpura horst block indicate the presence of partial melts J saline fluids to the north and south of the horst structure. Studies across the Indus-Tsangpo Suture (ITS) and Shyok Suture Zone have shown a highly conductive crust beneath the ITS and adjoining Tso-Morari dome. The Ladakh and Karakoram batholiths are delineated as high resistivity bodies with no obvious roots beneath. Several similarities between these observations and those in the Lhasa block, about 1500 km east of the NW Himalaya, are indicative of a predominantly two-dimensional nature of the Himalayan collision belt.
Keywords: Magnetotelluric techniques; Electrical conductivity; Resistivity; Indian lithospheric domains; Dharwar region